LEGAL PROTECTION AGAINST HOLDERS OF REGISTERED BRAND "PUMA AND CAT JUMPING" FOR SIMILARITY TO FAMOUS BRANDS - Dewi Putri Wibowo, Sabrina; Amalia, Lia; Abas, Muhamad (Awang Long Law Review, 2024)
This research focuses on two important aspects: The research will delve deeply into laws related to well-known brands in Indonesia and the research will analyze specific cases that have been decided by the courts, such as case Number 16/Pdt.Sus-HKI/Brand/2023/PN Niaga Jkt.Pst.Well-known brands are usually highly valued because they spend money on advertising and promotion, and become more popular around the world. In addition, it obtains legal protection through trademark registration in different countries, which gives them exclusive rights to their trademarks and allows others to use them illegally. The Trademark Law in Indonesia provides special protection for well-known brands. However, trademark infringement still occurs in Indonesia. Normative juridical research, with legislation and case approaches on legal protection of well-known brands in Indonesia. Result: The Trademark Law provides a clear framework for the legal protection of well-known trademarks in Indonesia, both preventively and restrictively, in particular Article 21, Article 83 and Explanation of Article 76 paragraph (2). In decision Number 16/Pdt.Sus-HKI/Brand/2023/PN Niaga Jkt.Pst, the Commercial Court considered evidence showing that the Defendant deliberately took advantage of the reputation of the "PUMA and Jumping Cat" brand without permission or license. The Commercial Court decided to cancel the registration of the Defendant's trademark "PUMA and Jumping Cats" because the action infringed the Plaintiff's trademark rights. This decision was made to protect the Claimant from its legitimate trademark rights.